VD_FINDINFO Décision / 2012 / 971 vom 25. Juni 2012 - VD Tribunal cantonal (2012)
CONDITION DE RECEVABILITÉ, PARTIE CIVILE, DÉCISION DE RENVOI, TRIBUNAL CIVIL | 41 CO, 73 al. 1 CO, 126 CPP (CH), 398 al. 5 CPP (CH)